Composition for preparing self-assembled monolayer, hole transport layer, perovskite solar cell, and preparation method and application thereof
Patent Information
- Application Number
- CN202510526947.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0021]本发明具有以下有益效果:通过SAM可与基底表面的羟基或与基底上的氧化镍表面的羟基以化学键形成自组装单分子层,从而能够抑制表面缺陷,同时形成界面偶极子,改善能级对准,并且通过特定选择的不同带隙的单分子层材料,提高了自组装单分子层的浸润性,优化了能级排列,提高了电荷提取能力,钝化界面缺陷,同时提高电池的开路电压和填充因子,从而提高了电池效率。
Smart Images

Figure CN122995403A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy materials technology, and more specifically, to a composition for preparing a self-assembled monolayer, a hole transport layer, a perovskite solar cell, a method for preparing the same, and its applications. Background Technology
[0002] Perovskite solar cells (PSCs), as an emerging photovoltaic technology, have made significant progress in photovoltaic performance in recent years, with their power conversion efficiency (PCE) exceeding 26% over the past decade. This high efficiency makes them a promising candidate for solar power generation. PSCs typically employ a pin structure, where energy losses at the hole transport layer (HTL)-perovskite (PVK) interface directly affect the overall efficiency of the device.
[0003] Therefore, how to solve the energy loss at the hole transport layer and perovskite interface, while simultaneously improving the open-circuit voltage and fill factor, and thus enhancing the performance of perovskite solar cell devices, is an urgent problem to be solved.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a composition for preparing a self-assembled monolayer, a hole transport layer, a perovskite solar cell, a method for preparing the same, and its application, so as to improve the above-mentioned technical problems.
[0006] This invention is implemented as follows:
[0007] In a first aspect, the present invention provides a composition for preparing a self-assembled monolayer, comprising a first self-assembled monolayer material and a second self-assembled monolayer material, wherein the structural formula of the first self-assembled monolayer material is: The structural formula of the second self-assembled monolayer material is: Where m is selected from integers from 1 to 5, and n is selected from integers from 1 to 7.
[0008] In a preferred embodiment, the structural formula of the first self-assembled monolayer material is:
[0009] In a preferred embodiment, the structural formula of the first self-assembled monolayer material is as follows: The second self-assembled monolayer material is selected from At least one of them;
[0010] In a preferred embodiment, the second self-assembled monolayer material is A mixture, preferably The molar ratio is 4:(5-7).
[0011] In a preferred embodiment, the molar ratio of the first self-assembled monolayer material to the second self-assembled monolayer material is (7-4):(3-6).
[0012] Secondly, the present invention also provides a hybrid self-assembled monomolecular material hole transport layer, which includes a self-assembled monomolecular layer formed using the above-mentioned composition as a raw material.
[0013] In a preferred embodiment, the hybrid self-assembled monomolecular material hole transport layer further includes a nickel oxide layer, wherein the self-assembled monomolecular layer is located on the surface of the nickel oxide layer.
[0014] Thirdly, the present invention also provides a method for preparing the above-mentioned hybrid self-assembled monomolecular material hole transport layer, which includes: directly coating the self-assembled monomolecular layer onto a substrate;
[0015] Alternatively, the nickel oxide layer can be prepared by first coating the substrate surface, and then the self-assembled monolayer can be prepared by coating the nickel oxide layer surface.
[0016] In a preferred embodiment, the substrate is cleaned and dried multiple times before surface coating is applied.
[0017] In a preferred embodiment, the preparation of the self-assembled monolayer includes: uniformly coating a solution containing the first self-assembled monolayer material and the second self-assembled monolayer material onto the surface to be coated, and then annealing.
[0018] Fourthly, the present invention also provides a perovskite solar cell comprising an assembled monomolecular material hole transport layer formed from the above-mentioned mixture as raw material.
[0019] Fifthly, the present invention also provides a method for preparing the above-mentioned perovskite solar cell, which includes: preparing a hole transport layer of the above-mentioned hybrid self-assembled monomolecular material on the surface of a substrate, and then sequentially preparing a perovskite layer, an electron transport layer and an electrode on the surface of the hole transport layer of the hybrid self-assembled monomolecular material.
[0020] In a sixth aspect, the present invention also provides applications of the above-described perovskite solar cells in consumer electronics, photovoltaic buildings, or transportation vehicles.
[0021] The present invention has the following beneficial effects: SAM can form a self-assembled monolayer by chemical bonding with hydroxyl groups on the substrate surface or with hydroxyl groups on the nickel oxide surface on the substrate, thereby suppressing surface defects, forming interfacial dipoles, improving energy level alignment, and improving the wettability of the self-assembled monolayer by specifically selecting monolayer materials with different band gaps, optimizing energy level arrangement, improving charge extraction capability, passivating interfacial defects, and improving the open-circuit voltage and fill factor of the battery, thereby improving battery efficiency. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the perovskite solar cell structure of the present invention;
[0024] Figure 2 This is a comparison diagram of the open-circuit voltage of the perovskite solar cell devices corresponding to Examples 1-4 and Comparative Examples 1-2 of the present invention;
[0025] Figure 3 The diagram shows a comparison of the short-circuit currents of perovskite solar cells corresponding to Examples 1-4 and Comparative Examples 1-2 of the present invention.
[0026] Figure 4 This is a comparison chart of the fill factor of perovskite solar cells corresponding to Examples 1-4 and Comparative Examples 1-2 of the present invention;
[0027] Figure 5 This is a comparison chart of the power conversion efficiency of perovskite solar cells corresponding to Examples 1-4 and Comparative Examples 1-2 of the present invention;
[0028] Figure 6 This is a comparison diagram of the open-circuit voltages of perovskite solar cells corresponding to Comparative Examples 1-4 of the present invention;
[0029] Figure 7 This is a comparison diagram of the short-circuit current of the perovskite solar cells corresponding to Comparative Examples 1-4 of the present invention.
[0030] Figure 8 This is a comparison chart of the fill factor of perovskite solar cells corresponding to Comparative Examples 1-4 of the present invention;
[0031] Figure 9This is a comparison chart of the power conversion efficiency of perovskite solar cells corresponding to Comparative Examples 1-4 of this invention. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0033] The following is a detailed description of a composition for preparing a self-assembled monolayer, a hole transport layer, a perovskite solar cell, a preparation method thereof, and its application disclosed in this invention.
[0034] Some embodiments of the present invention include a composition for preparing a self-assembled monolayer, comprising a first self-assembled monolayer material and a second self-assembled monolayer material, wherein the structural formula of the first self-assembled monolayer material is: The structural formula of the second self-assembled monolayer material is: Wherein, m is selected from an integer from 1 to 5, such as 1, 2, 3, 4 or 5, preferably m is selected from 1 or 2, and n is selected from an integer from 1 to 7, such as 1, 2, 3, 4, 5, 6 or 7, preferably n is selected from an integer from 2 to 4.
[0035] Self-assembled monolayers (SAMs) can effectively improve charge extraction capability and passivate interface defects. SAMs form self-assembled monolayers by chemically bonding with hydroxyl groups on the substrate or nickel oxide surface, thereby suppressing surface defects and forming interfacial dipoles to improve energy level alignment. Furthermore, by selecting two self-assembled monolayer materials with different band gaps, particularly using the methoxy groups present in the second self-assembled monolayer material in conjunction with the first self-assembled monolayer material, the wettability of the self-assembled monolayer is improved, the energy level arrangement is optimized, charge extraction capability is enhanced, interface defects are passivated, and the open-circuit voltage and fill factor of the battery are increased, thus improving battery efficiency.
[0036] It should be noted that the reasons for choosing a second self-assembled monolayer material with 2,7-position substituted methoxy groups (e.g., DC-PA) instead of a second self-assembled monolayer material with 3,6-position substituted methoxy groups (e.g., MeO-2PACz) are as follows: 1) According to experimental results, DC-PA can significantly improve the fill factor (FF) of the battery, better than MeO-2PACz with 3,6-position substituted methoxy groups and some other SAM materials; 2) Compared to MeO-2PACz with 3,6-position substituted methoxy groups, the 2,7-position substituted methoxy groups help reduce the electron-donating intensity, which can shift the highest occupied molecular orbital (HOMO) energy level downward and increase the molecular dipole moment. This allows for better alignment with the perovskite's valence band maximum (VBM), effectively improving the energy level alignment problem between the hole transport layer and the perovskite, thus achieving minimal energy level shift. In summary, DC-PA has the advantages of ordered energy levels and a good dipole moment.
[0037] Furthermore, to achieve better battery efficiency, the first self-assembled monolayer material can be selected as:
[0038] The composition of the self-assembled monolayer was further optimized, and the first self-assembled monolayer material was... The second self-assembled monolayer material is selected from: (DC-PA) or (Me-4PACz).
[0039] Furthermore, in some embodiments, the second self-assembled monolayer material is a mixture of DC-PA and Me-4PACz, preferably with a molar ratio of DC-PA to Me-4PACz of 4:(5 to 7), and exemplarily 4:6.
[0040] Me-4PACz's HOMO optimization of energy levels enables highly efficient charge transfer (significantly improving the open-circuit voltage (VOC)). The MeO-substituted phosphate group SAM material effectively enhances the connection with the perovskite layer, improving wettability. Me-4PACz alleviates the stability issues of DC-PA, while the short-chain DC-PA fills the gaps in the long-chain Me-4PACz. Furthermore, because the DC-PA molecular chain is shorter, its phosphate groups do not affect the anchoring of the phosphate groups in Me-4PACz, improving its conventional arrangement and resulting in a high-density, more uniform, and orderly arrangement of SAM, thus improving wettability, better substrate coverage, reducing defects, and improving the crystallinity of the perovskite film. This facilitates hole carrier extraction, resulting in the highest efficiency.
[0041] Furthermore, by using a specific ratio of Me-4PACz and DC-PA, the anchoring strength and packing density of the mixed SAM on the substrate can be effectively controlled, providing superior film coverage and better passivation of the perovskite layer.
[0042] In some implementations, in order to achieve better battery efficiency, the first self-assembled monolayer material should be used as the main material, that is, the molar ratio of the first self-assembled monolayer material to the second self-assembled monolayer material is (7-4):(3-6).
[0043] Some embodiments of the present invention provide a hybrid self-assembled monomolecular material hole transport layer, which includes a self-assembled monomolecular layer formed from the above-described composition.
[0044] In some embodiments, the hybrid self-assembled monomolecular material hole transport layer further includes a nickel oxide layer, with the self-assembled monomolecular layer located on the surface of the nickel oxide layer.
[0045] Nickel oxide is often used as a hole transport layer due to its good stability. However, surface defects such as hydroxyl groups on the nickel oxide surface can lead to nonradiative recombination and charge accumulation at the interface between the nickel oxide hole transport layer and the perovskite, reducing the efficiency and stability of PSCs. Therefore, self-assembled monomolecules can chemically bond with hydroxyl groups on the nickel oxide surface to form a self-assembled monolayer, thereby suppressing surface defects and forming interfacial dipoles to improve energy level alignment. Some embodiments of the present invention also provide a method for preparing a hybrid self-assembled monomolecule hole transport layer as described in the foregoing embodiments, which includes: directly preparing a self-assembled monolayer on a substrate surface; or, first coating a nickel oxide layer on the substrate surface, and then coating a self-assembled monolayer on the nickel oxide layer surface. Specifically, the method for preparing a hybrid self-assembled monomolecule hole transport layer includes the following steps:
[0046] S1. Prepare a precursor solution for the mixed self-assembled molecular layer.
[0047] The first and second self-assembled monolayer materials were dissolved separately in ultra-dry ethanol. After shaking at room temperature, first and second solutions were obtained, respectively. The first and second solutions were mixed in a certain proportion to obtain the precursor solution of the mixed self-assembled monolayer. The solute to solvent ratio of the first and second solutions was 0.4 to 1.0 mg (e.g., 0.5 mg) of the first or second self-assembled monolayer material per 1 mL of ultra-dry ethanol, and the shaking time was 25 to 35 min.
[0048] S2, Clean the substrate.
[0049] In some implementations, the substrate may be an FTO glass substrate. Before coating the substrate surface to prepare the nickel oxide layer, the substrate needs to be cleaned and dried multiple times. The substrate surface may have grease or fingerprint residue. These contaminants can hinder the chemical bonding between nickel oxide molecules and the substrate, leading to film defects or reduced adhesion.
[0050] Specifically, the FTO glass substrate is cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for at least 30 minutes, the cleaned glass substrate is dried with argon gas, and then cleaned with ultraviolet ozone for at least 30 minutes.
[0051] S3. Prepare the hole transport layer.
[0052] Specifically, in some embodiments, a nickel oxide solution is coated onto a cleaned substrate and then annealed; then a solution containing a first self-assembled monolayer material and a second self-assembled monolayer material is uniformly coated onto the surface of the nickel oxide layer and then annealed.
[0053] Furthermore, in some embodiments, 5–20 mg / mL of NiO is used. x The solution was spin-coated onto a cleaned substrate at 4000 rpm for 30 seconds, followed by annealing at 120–200°C for 10–20 minutes. Then, the prepared mixed SAM was spin-coated at 3000–4000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes. Spin-coating offers uniformity, controllability, and high efficiency, enabling the fabricated perovskite solar cells to achieve high conversion efficiency.
[0054] Furthermore, some embodiments of the present invention also provide a perovskite solar cell comprising a hybrid self-assembled monomolecular material hole transport layer as described in the foregoing embodiments. Exemplarily, the layer structure of this perovskite solar cell is as follows: Figure 1 As shown.
[0055] Furthermore, some embodiments of the present invention also provide a method for preparing the above-mentioned perovskite solar cell, which includes: preparing a hole transport layer of the aforementioned hybrid self-assembled monomolecular material on the surface of a substrate, and then sequentially preparing a perovskite layer, an electron transport layer, and an electrode on the surface of the hole transport layer of the hybrid self-assembled monomolecular material.
[0056] Some embodiments of the present invention also provide applications of perovskite solar cells as described in the foregoing embodiments in consumer electronics, photovoltaic buildings, or transportation vehicles.
[0057] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0058] Example 1
[0059] This embodiment provides a method for preparing a hole transport layer of a hybrid self-assembled monomolecular material, which includes the following steps:
[0060] (1) Weigh 2 mg Me-4PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 1). Weigh 2 mg DC-PA and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 2). Mix the two solutions at a volume ratio of solution 1: solution 2 = 8:2 to obtain a precursor solution of the mixed self-assembled molecules.
[0061] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0062] (3) Preparation of HTL: 10 mg / mL NiO x The mixture was spin-coated onto a clean substrate at 4000 rpm for 30 seconds and then annealed at 150°C for 10 minutes. The prepared mixed SAM was then spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 5 minutes.
[0063] Example 2
[0064] This embodiment provides a method for preparing a hole transport layer of a hybrid self-assembled monomolecular material, which includes the following steps:
[0065] (1) Weigh 2 mg Me-4PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 1). Weigh 2 mg DC-PA and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 2). Mix the two solutions at a volume ratio of solution 1: solution 2 = 6:4 to obtain a precursor solution of the mixed self-assembled molecules.
[0066] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0067] (3) Preparation of HTL: 10 mg / mL NiO x The mixture was spin-coated onto a clean substrate at 4000 rpm for 30 seconds and then annealed at 150°C for 10 minutes. The prepared mixed SAM was then spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 5 minutes.
[0068] Example 3
[0069] This embodiment provides a method for preparing a hole transport layer of a hybrid self-assembled monomolecular material, which includes the following steps:
[0070] (1) Weigh 2 mg Me-4PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 1). Weigh 2 mg DC-PA and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 2). Mix the two solutions thoroughly at a volume ratio of solution 1: solution 2 = 4:6 to obtain a precursor solution of the mixed self-assembled molecules.
[0071] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0072] (3) Preparation of HTL: 10 mg / mL NiO x The mixture was spin-coated onto a clean substrate at 4000 rpm for 30 seconds and then annealed at 150°C for 10 minutes. The prepared mixed SAM was then spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 5 minutes.
[0073] Example 4
[0074] This embodiment provides a method for preparing a hole transport layer of a hybrid self-assembled monomolecular material, which includes the following steps:
[0075] (1) Weigh 2 mg Me-4PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 1). Weigh 2 mg DC-PA and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min (referred to as solution 2). Mix the two solutions at a volume ratio of solution 1: solution 2 = 2:8 to obtain a precursor solution of the mixed self-assembled molecules.
[0076] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0077] (3) Preparation of HTL: 10 mg / mL NiO x The mixture was spin-coated onto a clean substrate at 4000 rpm for 30 seconds and then annealed at 150°C for 10 minutes. The prepared mixed SAM was then spin-coated at 4000 rpm for 30 seconds and annealed at 100°C for 5 minutes.
[0078] Comparative Example 1
[0079] This comparative example provides a method for preparing a hole transport layer of a single self-assembled monomolecular material, which includes the following steps:
[0080] (1) Weigh 2 mg Me-4PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min to obtain a precursor solution of self-assembled molecules.
[0081] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0082] (3) Preparation of HTL: 10 mg / mL NiO x The solution was spin-coated onto a cleaned substrate at 4000 rpm for 30 seconds, followed by annealing at 150°C for 10 minutes. Then, the prepared Me-4PACz solution was spin-coated at 4000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes.
[0083] Comparative Example 2
[0084] This comparative example provides a method for preparing a hole transport layer of a single self-assembled monomolecular material, which includes the following steps:
[0085] (1) Weigh 2 mg of DC-PA and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min to obtain a precursor solution of self-assembled molecules.
[0086] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0087] (3) Preparation of HTL: 10 mg / mL NiO x The solution was spin-coated onto a cleaned substrate at 4000 rpm for 30 seconds, followed by annealing at 150°C for 10 minutes. Then, the prepared DC-PA solution was spin-coated at 4000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes.
[0088] Comparative Example 3
[0089] This comparative example provides a method for preparing a hole transport layer of a single self-assembled monomolecular material, which includes the following steps:
[0090] (1) Weigh 2 mg MeO-4PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min to obtain a precursor solution of a single self-assembled molecule.
[0091] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0092] (3) Preparation of HTL: 10 mg / mL NiO x The SAM was spin-coated onto a clean substrate at 4000 rpm for 30 seconds, followed by annealing at 150°C for 10 minutes. Then, the prepared single SAM was spin-coated at 4000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes.
[0093] Comparative Example 4
[0094] This comparative example provides a method for preparing a hole transport layer of a single self-assembled monomolecular material, which includes the following steps:
[0095] (1) Weigh 2 mg MeO-2PACz and dissolve it in 4 mL of ultra-dry ethanol. Shake at room temperature for 30 min to obtain a precursor solution of a single self-assembled molecule.
[0096] (2) Cleaning: The FTO glass substrate was cleaned three times in glass cleaning agent and deionized water respectively, then cleaned with anhydrous ethanol for 30 minutes, the cleaned glass substrate was dried with argon gas, and then cleaned with ultraviolet ozone for 30 minutes.
[0097] (3) Preparation of HTL: 10 mg / mL NiO x The SAM was spin-coated onto a clean substrate at 4000 rpm for 30 seconds, followed by annealing at 150°C for 10 minutes. Then, the prepared single SAM was spin-coated at 4000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes.
[0098] Example 5
[0099] This embodiment provides a method for fabricating a perovskite solar cell, the specific steps of which are as follows:
[0100] Perovskite layers (Cs) were prepared by flash evaporation on the surface of the hole transport layers prepared in the aforementioned embodiments and comparative examples, respectively. 0.22 FA 0.78 PbI 0.865 Br 0.135The substrate (thickness: 700 nm) was then annealed at 120 °C for 20 min. A passivation layer (PEAI, MAI, PHenHCl) was then spin-coated onto the annealed substrate and annealed at 100 °C for 5 min.
[0101] The sample with the perovskite layer prepared was placed in the coating machine cavity and C60 (13nm), BCP (0.7nm), and Cu (250nm) were deposited sequentially by thermal evaporation.
[0102] Test case
[0103] The perovskite solar cell prepared in Example 5 was subjected to performance testing. The specific testing method was as follows: the current density and voltage curves were measured under simulated sunlight at AM1.5.
[0104] The comparison charts of open-circuit voltage, short-circuit current, fill factor, and power conversion efficiency of the perovskite solar cells corresponding to Examples 1-4 and Comparative Examples 1-4 are as follows: Figure 2 , Figure 3 , Figure 4 , Figure 5 As shown, the comparison charts of open-circuit voltage, short-circuit current, fill factor, and power conversion efficiency of the perovskite solar cells corresponding to Examples 1-4 are as follows: Figure 6 , Figure 7 , Figure 8 , Figure 9 As shown.
[0105] In Comparative Example 1, a first self-assembled monolayer material with m=1 and n=4 in the structural formula was used. The SAM material used in this example showed a higher open-circuit voltage, representing the highest open-circuit voltage among all SAM materials used, with a maximum open-circuit voltage of 1.27V. Comparative Example 2 used a second type of self-assembled monolayer material according to the patent embodiment, where m=1 and n=4. Its open-circuit voltage was lower than Me-4PACz, and its fill factor was lower than both Me-4PACz and DC-PA. Comparative Example 3 used a first type of self-assembled monolayer material according to the patent embodiment, where m=1 and n=2. The SAM material used in this example showed a higher fill factor, representing the highest fill factor among all SAM materials used, with a maximum fill factor of 86.35%. The SAM material used in Comparative Example 4 is the second type of the second self-assembled monolayer material in the specific embodiment of the patent, where m=1 and n=2. The SAM material used in this example differs from the SAM material described in Example 7 in that the methoxy substitution position is different, its open circuit voltage is not as high as the above three SAM materials, and its fill factor is not as high as DC-PA.
[0106] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A composition for preparing a self-assembled monolayer, characterized in that, It includes a first self-assembled monolayer material and a second self-assembled monolayer material, the structural formula of which is: The structural formula of the second self-assembled monolayer material is: Where m is selected from integers from 1 to 5, and n is selected from integers from 1 to 7.
2. The composition according to claim 1, characterized in that, The first self-assembled monolayer material is:
3. The composition according to claim 2, characterized in that, The structural formula of the first self-assembled monolayer material is as follows: The second self-assembled monolayer material is selected from At least one of them; Preferably, the second self-assembled monolayer material is and A mixture, preferably The molar ratio is 4:(5-7).
4. The composition according to any one of claims 1 to 3, characterized in that, The molar ratio of the first self-assembled monolayer material to the second self-assembled monolayer material is (7-4):(3-6).
5. A hybrid self-assembled monomolecular material hole transport layer, characterized in that, It includes a self-assembled monolayer formed using the composition of any one of claims 1 to 4 as a raw material.
6. The hybrid self-assembled monomolecular material hole transport layer according to claim 5, characterized in that, The hybrid self-assembled monomolecular material hole transport layer further includes a nickel oxide layer, wherein the self-assembled monomolecular layer is located on the surface of the nickel oxide layer.
7. A method for preparing a hybrid self-assembled monomolecular material hole transport layer as described in claim 5 or 6, characterized in that, It includes: The self-assembled monolayer is directly coated onto the substrate; Alternatively, a nickel oxide layer may be first coated onto the substrate surface, and then the self-assembled monolayer may be coated onto the nickel oxide layer surface. Preferably, the substrate is cleaned and dried multiple times before surface coating is applied. Preferably, the preparation of the self-assembled monolayer includes: uniformly coating a solution containing the first self-assembled monolayer material and the second self-assembled monolayer material onto the surface to be coated, and then annealing.
8. A perovskite solar cell, characterized in that, It includes a hybrid self-assembled monomolecular material hole transport layer as described in claim 5 or 6.
9. The method for preparing a perovskite solar cell as described in claim 8, characterized in that, It includes: A hybrid self-assembled monomolecular material hole transport layer as described in claim 5 or 6 is prepared on the surface of a substrate, and then a perovskite layer, an electron transport layer, and an electrode are sequentially prepared on the surface of the hybrid self-assembled monomolecular material hole transport layer.
10. The application of the perovskite solar cell as described in claim 8 in consumer electronics, photovoltaic buildings, or transportation vehicles.